Finding distinctions between oral cancer and periodontitis using saliva metabolites and machine learning. (7th September 2020) - Kouznetsova, Valentina L.; Li, Jeremy; Romm, Eden; Tsigelny, Igor F.
Abstract: Objective: The aim of this research is the study of metabolic pathways related to oral cancer and periodontitis along with development of machine‐learning model for elucidation of these diseases based on saliva metabolites of patients. Methods: Data mining, metabolomic pathways analysis, study of metabolite–gene networks related to these diseases. Machine‐learning and deep‐learning methods for development of the model for recognition of oral cancer versus periodontitis, using patients' saliva. Results: The most accurate classifications between oral cancer and periodontitis were performed using neural networks, logistic regression and stochastic gradient descent confirmed by the separate 10‐fold cross‐validations. The best results were achieved by the deep‐learning neural network with the TensorFlow program. Accuracy of the resulting model was 79.54%. The other methods, which did not rely on deep learning, were able to achieve comparable, although slightly worse results with respect to accuracy. Conclusion: Our results demonstrate a possibility to distinguish oral cancer from periodontal disease by analysis the saliva metabolites of a patient, using machine‐learning methods. These findings may be useful in the development of a non‐invasive method to aid care providers in determining between oral cancer and periodontitis quickly and effectively.